2013
DOI: 10.1159/000356691
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Repetitive DNA in <b><i>Semaprochilodus </i></b>(Characiformes, Prochilodontidae): A Fish Model for Sex Chromosome Differentiation

Abstract: Distribution of 6 microsatellites and 5 transposable elements on the chromosomes of Semaprochilodus taeniurus and S. insignis, commonly referred to as Jaraqui, was performed using their physical mapping with fluorescence in situ hybridization. In this study, we aim to understand the evolutionary dynamics in genomes of S. taeniurus and S. insignis by comparing the position, abundance and contribution of the repetitive sequences in the origins and differentiation of a ZZ/ZW sex chromosome system in S. taeniurus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
6
16
0
Order By: Relevance
“…Coincidently, it is also the only species in our study that exhibited a fully heterochromatic W chromosome, suggesting an association between heterochromatinization and (TTA) 10 accumulation. Consistent with this result, previous studies have shown greater SSR accumulation in the heterochromatic areas of the sex-specific chromosome [Pokorná et al, 2011;Cioffi et al, 2012;Poltronieri et al, 2013;Terencio et al, 2013;Nanda et al, 2014;Yano et al, 2014;Ziemniczak et al, 2014]. However, we found that all other SSRs clustered to either euchromatic or heterochromatic regions of the sex chromosomes, indicating that they are not necessarily associated with heterochromatin accumulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Coincidently, it is also the only species in our study that exhibited a fully heterochromatic W chromosome, suggesting an association between heterochromatinization and (TTA) 10 accumulation. Consistent with this result, previous studies have shown greater SSR accumulation in the heterochromatic areas of the sex-specific chromosome [Pokorná et al, 2011;Cioffi et al, 2012;Poltronieri et al, 2013;Terencio et al, 2013;Nanda et al, 2014;Yano et al, 2014;Ziemniczak et al, 2014]. However, we found that all other SSRs clustered to either euchromatic or heterochromatic regions of the sex chromosomes, indicating that they are not necessarily associated with heterochromatin accumulation.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, it has been postulated that microsatellite accumulation in eukaryotic genomes is nonrandom and that each group of organisms/species show preferential accumulation of specific SSR motifs with a particular chromosomal distribution [Tóth et al, 2000;Ruiz-Ruano et al, 2015]. The (CA) 15 , (GA) 15 and (CG) 15 SSRs were previously mapped in different characiform fishes and had similar subtelomeric distributions in Hoplias , Leporinus and Triportheus species, while 2 Semaprochilodus species showed few centromeric/subtelomeric signals [Cioffi et al, 2011[Cioffi et al, , 2012Poltronieri et al, 2013;Terencio et al, 2013;Yano et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns of random microsatellite distribution have been recently reported in other Orthopteran species, i.e., the grasshoppers Abracris flavolineata (Milani and Cabral-de-Mello 2014) and Ronderosia bergi (Palacios-Gimenez et al in preparation), although for some repeats, in addition to disperse signals, specific enriched regions were also observed, indicating distinct patterns of accumulation at the intragenomic and interspecific level. Similar dispersal patterns of microsatellite arrays and specific localization in sex chromosomes have been previously reported in other eukaryotes, such as plants (Kubat et al 2008;Kejnovský et al 2013), reptiles (Pokorná et al 2011;Matsubara et al 2013) and fish (Terencio et al 2013), and some authors have highlighted a role for this class of sequence in sex chromosome differentiation (see for example Kubat et al 2008;Pokorná et al 2011;Kejnovský et al 2013;Matsubara et al 2013).…”
Section: Discussionsupporting
confidence: 77%
“…These regions can be hotspots for the accumulation of SSRs and might be associated with the structural formation of the telomere and participate in chromosome rearrangements as proposed for Semaprochilodus [Terencio et al, 2013]. The same subterminal pattern was seen for (CG) 15 and (TA) 15 probes, but only in C. gomesi.…”
Section: Localization Of Microsatellites In the C Zebra And C Gomessupporting
confidence: 55%